2008 IEEE International Reliability Physics Symposium 2008
DOI: 10.1109/relphy.2008.4558983
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive reliability analysis of CoWP Metal Cap unit processes for high volume production in sub-μm dimensions

Abstract: INTRODUCTIONReliability of copper interconnect systems is very sensitive to the maximum current used in the product. Shrinking the metal dimensions from technology node to technology node yields a need for higher current density to fulfill the product needs. Since the electromigration performance is predicted to decrease for 45nm and beyond [1], higher electromigration robustness in smaller dimensions is necessary. A main driving force for electromigration improvement is engineering the interface quality/compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…This result supports the observation of highly disordered Cu/SiN x interfaces and highly ordered, dominantly metallic bonding Cu/Co interfaces 12 . The EM lifetime improvement by using the CoWP cap observed in this study is consistent with the results reported previously 7,8,13 . In addition, the results showed a clear grain size effect on EM lifetime for both cap layers.…”
Section: Methodssupporting
confidence: 93%
“…This result supports the observation of highly disordered Cu/SiN x interfaces and highly ordered, dominantly metallic bonding Cu/Co interfaces 12 . The EM lifetime improvement by using the CoWP cap observed in this study is consistent with the results reported previously 7,8,13 . In addition, the results showed a clear grain size effect on EM lifetime for both cap layers.…”
Section: Methodssupporting
confidence: 93%
“…The results show an improved lifetime by a factor of two for ACP and a factor of 100 for metal cap samples compared to standard processing. Additionally to that we found an activation energy improvement of 0.1eV for ACP and > 0.4eV for MC compared to standard processing [11].…”
Section: A Electromigration Resultssupporting
confidence: 73%
“…To compensate, analogs of the techniques used to improve Al The data indicate that current density exponent can vary between 1 and 2 depending on the relative importance of void nucleation and growth to the failure time. electromigration performance have been introduced for Cu: namely, Cu alloys to limit fast grain boundary diffusion [79][80][81][82][83][84], which controls the rate of electromigration in highly scaled Cu, and the incorporation of metallic cap layers at the Cu surface to impede diffusion along the top surface of the Cu [85,86].…”
Section: Electromigrationmentioning
confidence: 99%